Understanding Indonesian People through Literature: Indigenous Psycho-Sociology Perspectives - Ahmadi, Anas; Darni; Yulianto, Bambang (International Journal of Criminology and Sociology, 2021)
Indigenous studies are currently attracting humanities researchers, one of which is the field of literature. Literary researchers explore the locality contained in literary texts through the perspective of indigenous studies. In this regard, this study explored Indonesian literature through the perspective of indigenous studies. The theory used in this study was literary criticism associated with indigenous psychology and indigenous sociology. The data source used was the Rafilus novel written by Budi Darma. The research method used was qualitative because the researchers emphasized the interpretation of the text. Data analysis techniques included the stages of indexation, reduction, exposure, and interpretation. The results showed that the character Rafilus displays the psychological side of indigenous people of Java through segmentation: friendliness dan politeness in life, self-awareness in life, a simple life desire, and loves to learn.